Plural Marking in Mahshahri, an Iranian Dialect on the Northern Coast of the Persian Gulf - Reza Amini; Yazdan Choubsaz (مطالعات زبان‌‌ها و گویش‌های غرب ایران)
In this article, the plural marker in the Mahshahri dialect is examined. Mahshahri is the native language of the people of Bandar-e Mahshahr. This dialect has close similarities with other Iranian language varieties spoken in southern Iran, particularly those of other southern cities of Khuzestan Province, and Iranian language varieties of Bushehr, Fars and Kohkiluye and Boyr-Ahmad provinces. From a methodological point of view, this research is descriptive and analytical. The research data were mainly obtained through a questionnaire and by examining the text of a twenty-minute continuous speech from the Mahshahri dialect. The investigations carried out in this article show that the plural marker of Mahshahri is /-æl/, which, based on the phonetic environment of the base to which it is added, can have other allomorphic manifestations as well. The conducted studies also indicate that there are variations in the use of the plural marker in the Mahshahri dialect. These variations, in many cases, align with the replacement of the marker with its standard Persian counterparts. Therefore, the variations that can be seen in the use of the plural marker of Mahshahri can be considered in line with other current changes that are underway in the direction of leveling the dialect with standard Persian in Iran.